Safety and immunogenicity of a modified vaccinia Ankara-based HIV-1 vaccine (MVA-B) in HIV-1-infected patients alone or in combination with a drug to reactivate latent HIV-1. (26th February 2015) - Mothe, Beatriz; Climent, Nuria; Plana, Montserrat; Rosàs, Miriam; Jiménez, José Luis; Muñoz-Fernández, María Ángeles; Puertas, María C.; Carrillo, Jorge; Gonzalez, Nuria; León, Agathe; Pich, Judit; Arnaiz, Joan Albert; et al.
Abstract: Objectives: The safety, immunogenicity, impact on the latent reservoir and rebound of viral load after therapeutic HIV-1 vaccination with recombinant modified vaccinia Ankara-based (MVA-B) HIV-1 vaccine expressing monomeric gp120 and the fused Gag-Pol-Nef polyprotein of clade B with or without a drug to reactivate latent HIV-1 (disulfiram) were assessed. Methods: HIV-1-infected patients were randomized to receive three injections of MVA-B ( n = 20) or placebo ( n = 10). Twelve patients (eight who received vaccine and four who were given placebo) received a fourth dose of MVA-B followed by 3 months of disulfiram. Combined ART (cART) was discontinued 8 weeks after the last dose of MVA-B. Clinical Trials.gov identifier: NCT01571466. Results: MVA-B was safe and well tolerated. A minor, but significant, increase in the T cell responses targeting vaccine inserts of Gag was observed [a median of 290, 403 and 435 spot-forming-cells/10 6 PBMCs at baseline, after two vaccinations and after three vaccinations, respectively; P = 0.02 and P = 0.04]. After interruption of cART, a modest delay in the rebound of the plasma viral load in participants receiving vaccine but not disulfiram was observed compared with placebo recipients ( P = 0.01). The dynamics of the viral load rebound did not change in patients receiving MVA-B/disulfiram. No changes in the proviral reservoir were observed after disulfiram treatment. Conclusions: MVA-B vaccination was a safe strategy to increase Gag-specific T cell responses in chronically HIV-1-infected individuals, but it did not have a major impact on the latent reservoir or the rebound of plasma viral load after interruption of cART when given alone or in combination with disulfiram.